Residents’ Perceptions on Tourism Impacts and Quality of Life: The Case of Faro - Roberts, Taya; Renda, Ana Isabel; Pinto, Patricia (Journal of Tourism, Sustainability and Well-being, 2022)
This work addresses the problem of resident’s perceptions of tourism impacts and their perceptions of quality of life. Although there is a growing bank of tourism research available on these topics, specific tourism locations still need to be studied. The main goal of this research was to determine the tourism impacts in Faro, Algarve and whether links could be established between tourism impacts (positive and negative) and residents’ perceptions of quality of life, globally, and within four domains, namely: material domain, community domain, health and safety domain and emotional domain. A sample of 300 residents was used to collect data from Faro residents on their perceptions of tourism impacts in their location, as well as the residents’ perceptions of their quality of life in the four domains. The results indicate a correlation between perceptions about tourism impacts and residents’ perceptions of quality of life within the four domains and globally. These findings open the way for a more holistic understanding of the location’s tourism environment and the interplay of tourism and the residents of the tourist location. These findings are beneficial to residents, policy planners, governing bodies and tourism operators.